Overweight and obese men are more prone to infertility-Myth or Fact? - Najafi, Mohsen; Kavitha, Papanna; Gopalappa, Sreenivasa; Thammaiah, Chaithra P.; Sathidevi, Vineeth V.; Malini, Suttur S. (Archives of Advances in Biosciences, 2011)
To investigate the association of sub-fertility/ infertility with increased BMI in overweight and obese men and in control group in Karnataka, South India. In this pilot study 20 overweight and obese men, aged 25-45, and 10 normal-weighed men with proven fertility were included. Both groups were married. All cases and controls were evaluated for different semen parameters according to World Health Organization (WHO) standards. Statistical analysis was performed using the SPSS software, version 16.0. P-values less than 0.05 were considered statistically significant. Different infertile conditions are evident among overweight and obese individuals recruited for this study. Variations in the semen parameter are significant in obese men compared to controls but sperm function test does not show statistical significant values in overweight and obese men when compared with control group. In case of oligoasthenospermic subjects pH shows a significant increase (p=0.002) compared to controls. Also the levels of Fructose show a significant decline in both azoospermic (p<0.001) and oligoasthenosermic (p=0.002) groups when compared to control group. With reference to the data obtained from this pilot study we found that increased BMI in men affects the semen quality which ultimately results in decreased fertility rate in men.